Conversing in Reflective Glory: A Systematic Study Using National Football League Games - Margolin, Drew; Liao, Wang; Lin, Yu-Ru (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
Conversations about a group can alter its structure and development. The antecedents of group-oriented conversation are difficult to pinpoint, however, because of the complex interdependence between individual and group behavior. In this study we utilize a unique set of exogenous, group-level treatments — the outcomes of National Football League games — to observe how group members — fans of these teams — participate in group-oriented conversation on Twitter. We show first that positive group outcomes (team victories) encourage group members to talk publicly about their group. Our results also indicate that group members participate more actively in the group-oriented discussion when the the outcome is a surprise. Future directions for this line of research are discussed.